Nutritional Screening and Assessment of Children with Congenital Heart Diseases: A Cross-Sectional Study in a Tertiary Level Hospital in Libya - Hawa Gamaa; Mohammed Abubaker (AlQalam Journal of Medical and Applied Sciences, 2025)
Congenital heart disease (CHD) is prevalent in Libyan children who are referred to a cardiac clinic tertiary center. These patients may experience mild malnutrition, which can progress to failure to thrive (FTT). Therefore, the aim of this paper is to determine the frequency of malnutrition and evaluate the nutritional status of children with congenital heart disease. The study adopted a descriptive cross-sectional design. It involved pediatric patients aged from 2 months to 18 years presented to the pediatric department at Ibn Sina Teaching Hospital with CHD. Data were collected over the period between April 2024 and September 2024. Subsequently, data was analyzed using the Statistical a Package for Social Science (Rstudio) version 2.3.2. Results showed that, 53.3% were males and 46.7% were females. The participants’ age ranged between (2.8-180) months with mean ± SD (29.5 ± 38.1) months. A total of 130 participants were found to have low weight-for-age or a low Body Mass Index (BMI). The prevalence of malnutrition among the participants was 32.8% additionally, 24.7% of the participants were wasted, and 38.6% were stunted. Conversely, 14.1% of children were classified as overweight, and obesity was observed in 5.1% of the participants. Malnutrition is remains highly prevalent among children with CHD. However, the management of nutritional status can be improved by providing patients with early nutritional counseling and conducting periodic nutritional status assessments. ينتشر مرض القلب الخلقي بين الأطفال الليبيين الذين يتم إحالتهم إلى المركز الثالث لعيادة القلب. قد يعاني هؤلاء المرضى من سوء التغذية الخفيف، والذي. يمكن أن يتطور إلى فشل النمو ولذلك فإن الهدف من هذه الورقة هو تحديد مدى أنتشار سوء التغذية وتقييم الحالة التغذوية للأطفال المصابين بأمراض القلب الخلقية. واعتمدت الدراسة التصميم الوصفي المقطعي. وقد شملت مرضى الأطفال الذين تتراوح أعمارهم بين شهرين إلى 18 عامًا والذين تم تقديمهم إلى قسم الأطفال في مستشفى ابن سينا التعليمي مصابين بأمراض القلب الخلقية. تم جمع البيانات خلال الفترة ما بين أبريل 2024 وسبتمبر 2024. وبعد ذلك، تم تحليل البيانات باستخدام الحزمة الإحصائية للعلوم الاجتماعية الإصدار 2.3.2. وأظهرت النتائج أن 53.3% ذكور و46.7% إناث. تراوحت أعمار المشاركين بين (2.8-180) شهرًا. تم العثور على إجمالي 130 مشاركًا لديهم انخفاض الوزن بالنسبة للعمر أو انخفاض مؤشر كتلة . كما بلغ معدل انتشار سوء التغذية بين المشاركين 32.8%، بالإضافة إلى ذلك، كان 24.7% من المشاركين يعانون من الهزال، و38.6% من التقزم. وعلى العكس من ذلك، تم تصنيف 14.1% من الأطفال على أنهم يعانون من زيادة الوزن، ولوحظت السمنة لدى 5.1% من المشاركين. لا يزال سوء التغذية منتشراً بشكل كبير بين الأطفال المصابين بأمراض القلب التاجية. ومع ذلك، يمكن تحسين إدارة الحالة التغذوية من خلال تزويد المرضى بالمشورة التغذوية المبكرة وإجراء تقييمات دورية للحالة التغذوية